Needle Direction and Distance of Arteriovenous Fistula Cannulation in Hemodialysis Adequacy; a Systematic Review and Meta-Analysis - Samad Karkhah; Majid Pourshaikhian; Pooyan Ghorbani Vajargah; Morteza Zaboli Mahdiabadi; Amirabbas Mollaei; Saman Maroufizadeh; Seyed Javad Hosseini; Joseph Osuji; Mohammad Taghi Moghadamnia (Archives of Academic Emergency Medicine, 2023)
Introduction: This systematic review and meta-analysis aimed to summarize the evidence regarding the impact of needle direction and distance of arteriovenous fistula (AVF) cannulation on KT/V (where k is the dialyzer urea clearance, t, the duration of dialysis, and V, the volume of distribution of urea) and access recirculation (AR) as hemodialysis (HD) adequacy criteria.